Role of adrenal vein sampling in primary aldosteronism: Impact of imaging, localization, and age. Issue 5 (21st January 2016) - Wachtel, Heather; Zaheer, Salman; Shah, Parth K.; Trerotola, Scott O.; Karakousis, Giorgos C.; Roses, Robert E.; Cohen, Debbie L.; Fraker, Douglas L.
Abstract : Background: The role of adrenal vein sampling (AVS) has been debated, with some authorities advocating selective use in younger patients (≤40 years), and those localized by preoperative imaging. We examined our experience to determine the impact of AVS in patients who routinely underwent AVS with a high success rate. Methods: A retrospective cohort study was performed using a prospectively maintained database of patients referred for evaluation of PA (1997–2013). Patients were classified as localized (L) if a unilateral mass was identified on imaging, and non‐localized (NL) otherwise. Results: Of 367 patients, 94% (n = 345) underwent successful AVS. Seventy‐two percent (n = 265) were L; AVS was lateralizing 58% (n = 214). AVS changed management in 43% of patients (n = 158). In patients ≤40 years, AVS changed management in 30% (n = 15). In patients ≤40 years with a ≥1 cm adrenal mass, 12% (n = 3) would have undergone unnecessary surgery based on imaging results alone; in patients >40 years with a ≥1 cm adrenal mass, 3% (n = 5) would have undergone wrong‐side surgery, and 30% (n = 50) would have undergone unnecessary surgery based on imaging. Conclusion: AVS changed management in a significant minority of patients regardless of age and imaging findings. AVS should be routinely recommended in all patients with PA, to direct operative therapy. J. Surg. Oncol. 2016;113:532–537 . © 2016 Wiley Periodicals, Inc.